Exigência energética e relação carboidrato:lipídio para alevinos de piracanjuba (Brycon orbignyanus) - Borba, Maude Regina de [UNESP] (2003)
Piracanjuba (Brycon orbignyanus) is a migratory fast-growing omnivore fish, which is threatened to extinction in Paraná and Uruguai River basis in Southern Brazil, due to dam building along the rivers and over exploitation of the stocks, among other factors. Therefore, efforts have been made to raise this fish in captivity for stock enhancement or commercial aquaculture. In the present study, two feeding trials were carried out in order to improve understanding about the bioenergetics of this species. In experiment 1, to determine the possible protein-sparing action of dietary lipid, and its effect on growth, lipogenesis and body composition of piracanjuba fingerlings, six purified diets were prepared combining two protein (30 and 32%) and three lipid concentrations (5.5%, 8.8% e 12.1%), in a factorial arrangement. Triplicate groups of eleven fish (11.3 ± 0.1g/fish) were held in 100-L aquaria supplied with recirculating freshwater, and fed to apparent satiation twice daily for 100 days. Fish daily weight gain, (DWG), daily feed consumption (% body weight, DFC), feed conversion ratio (FCR), protein efficiency ratio (PER), apparent net protein retention (ANPR), apparent net energy retention (ANER) and hepatosomatic index (HSI) were not influenced by dietary protein or lipid concentration (P>0.05). However, body composition was directly affected by dietary treatments (P<0.05). An increase in body fat and dry matter was observed as dietary lipid increased, for both dietary protein concentrations tested. The activity of fatty acid sinthetase enzyme was depressed (P<0.05) by increasing dietary fat levels, glucose-6-phosphate dehydrogenase activity did not differ among dietary treatments (P>0.05), and malic enzyme showed some modulation by dietary protein. The results indicated that an increase from 5.5 to 12.1% in the dietary lipid, at a protein concentration of 30 or 32%, promotes body fat accumulation...